Minimal anonimized SLCMV diagnostics data in Cambodia and Vietnam in 2016 - Minato, Nami; Sok, Sophearith; Chen, Songbi; Delaquis, Erik; Phirun, Iv; Burra, Dharani Dhar; Newby, Jonathan Craig; Wyckhuys, Kris A.G.; Haan, Stef de (International Center for Tropical Agriculture, 2019)
The data includes diagnosis results of Sri Lankan cassava mosaic virus (SLCMV) from binational surveys of 15 districts in Vietnam and 16 districts in Cambodia, with 240 samples by district.